Vascular smooth muscle cell senescence accelerates medin aggregation via small extracellular vesicle secretion and extracellular matrix reorganization. Issue 2 (25th November 2022) - Whitehead, Meredith; Yusoff, Syabira; Ahmad, Sadia; Schmidt, Lukas; Mayr, Manuel; Madine, Jillian; Middleton, David; Shanahan, Catherine M.
Abstract: Vascular amyloidosis, caused when peptide monomers aggregate into insoluble amyloid, is a prevalent age‐associated pathology. Aortic medial amyloid (AMA) is the most common human amyloid and is composed of medin, a 50‐amino acid peptide. Emerging evidence has implicated extracellular vesicles (EVs) as mediators of pathological amyloid accumulation in the extracellular matrix (ECM). To determine the mechanisms of AMA formation with age, we explored the impact of vascular smooth muscle cell (VSMC) senescence, EV secretion, and ECM remodeling on medin accumulation. Medin was detected in EVs secreted from primary VSMCs. Small, round medin aggregates colocalized with EV markers in decellularized ECM in vitro and medin was shown on the surface of EVs deposited in the ECM. Decreasing EV secretion with an inhibitor attenuated aggregation and deposition of medin in the ECM. Medin accumulation in the aortic wall of human subjects was strongly correlated with age and VSMC senescence increased EV secretion, increased EV medin loading and triggered deposition of fibril‐like medin. Proteomic analysis showed VSMC senescence induced changes in EV cargo and ECM composition, which led to enhanced EV‐ECM binding and accelerated medin aggregation. Abundance of the proteoglycan, HSPG2, was increased in the senescent ECM and colocalized with EVs and medin. Isolated EVs selectively bound to HSPG2 in the ECM and its knock‐down decreased formation of fibril‐like medin structures. These data identify VSMC‐derived EVs and HSPG2 in the ECM as key mediators of medin accumulation, contributing to age‐associated AMA development. Abstract : This study has elucidated how during ageing, VSMCs regulate medin accumulation via secretion of sEVs, changes in sEV cargoes and ECM composition. We showed that VSMC senescence increased secretion of sEVs and the accumulation of medin in the ECM by enhancing medin aggregation on the EV surface and enhancing EV binding to HSPG2 in the ECM. In addition, increased expression and deposition of HSPG2 in the aged ECM triggered formation of fibril‐like medin, further enhancing the development of AMA.